2023
DOI: 10.3390/molecules28062823
|View full text |Cite
|
Sign up to set email alerts
|

Biosurfactants: Forthcomings and Regulatory Affairs in Food-Based Industries

Abstract: The terms discussed in this review—biosurfactants (BSs) and bioemulsifiers (BEs)—describe surface-active molecules of microbial origin which are popular chemical entities for many industries, including food. BSs are generally low-molecular-weight compounds with the ability to reduce surface tension noticeably, whereas BEs are high-molecular-weight molecules with efficient emulsifying abilities. Some other biomolecules, such as lecithin and egg yolk, are useful as natural BEs in food products. The high toxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 81 publications
0
13
0
Order By: Relevance
“…All the BE/BS were active, with the zone of growth inhibition ranging from 3.70 ± 0.22 to 5.70 ± 0.12 mm against E. coli E1 and from 3.83 ± 0.40 to 4.85 ± 0.42 mm against S. aureus S1. This antibacterial activity might be due to the amphiphilic nature of BE/BS, which enables their penetration into the phospholipidic membranes of bacteria, leading to alteration of their permeability, loss of their electrochemical gradient, and leakage of essential molecules (Makovitzki et al, 2006 ; Mbawala et al, 2013 ; Mouafo, Sokamte, et al, 2023 ; Sharma et al, 2023 ). Disruption of the bacterial cell wall and pores' formation following interaction with biosurfactants, as reported by Mouafo, Mbawala, and Ndjouenkeu ( 2018 ) and Mouafo, Sokamte, et al ( 2023 ), could also explain the antimicrobial activity of BE/BS observed in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the BE/BS were active, with the zone of growth inhibition ranging from 3.70 ± 0.22 to 5.70 ± 0.12 mm against E. coli E1 and from 3.83 ± 0.40 to 4.85 ± 0.42 mm against S. aureus S1. This antibacterial activity might be due to the amphiphilic nature of BE/BS, which enables their penetration into the phospholipidic membranes of bacteria, leading to alteration of their permeability, loss of their electrochemical gradient, and leakage of essential molecules (Makovitzki et al, 2006 ; Mbawala et al, 2013 ; Mouafo, Sokamte, et al, 2023 ; Sharma et al, 2023 ). Disruption of the bacterial cell wall and pores' formation following interaction with biosurfactants, as reported by Mouafo, Mbawala, and Ndjouenkeu ( 2018 ) and Mouafo, Sokamte, et al ( 2023 ), could also explain the antimicrobial activity of BE/BS observed in this study.…”
Section: Resultsmentioning
confidence: 99%
“…This observation suggests a difference in the chemical composition and structure of the two BE/BS. Variation in the antibacterial activity of biosurfactants according to the producing strain has been reported in the literature (Adnan et al, 2023;Liu et al, 2015;Mouafo, Baomog, et al, 2020;Sharma et al, 2023).…”
Section: Antibacterial Activity Of Bioemulsifiers/ Biosurfactantsmentioning
confidence: 99%
“…It is possible to see that biosurfactants are currently used in many and different fields. For food applications, one of the biosurfactants with the highest potential for exploitation are the glycolipids, more precisely the rhamnolipids (Jiang et al, 2020;Sałek & Euston, 2019;Sharma et al, 2023).…”
Section: Properties and Applicationsmentioning
confidence: 99%
“…Thus, the purpose of the review is to focus on the applicability of mBS by emphasizing the versatile bioactive properties that they impart to the NE. Majority of related reviews have focused mainly on applications of mBS based NE in cosmetics (Ghosh et al, 2023;Karnwal et al, 2023;Singh et al, 2022), foods (Sharma et al, 2022;Sharma et al, 2023;Sneha & Kumar, 2022), pharmaceuticals (Ohadi, Shahravan, et al, 2020;Thakur et al, 2020), and so forth. The current review highlights the potential negative effects of NE prepared using conventional surfactants, the use of mBS as an alternative component of NE, their additional advantages in the preparation of NE and their varied applications.…”
Section: Introductionmentioning
confidence: 99%